Froth flotation giant surfactants. (24th January 2019) - Li, Zongxin; Fu, Yu; Li, Zhan; Nan, Nan; Zhu, Yimin; Li, Yiwen
Abstract: Whilst many efforts have been well documented on the readily available flotation surfactants, more kinds of newly-designed surfactants and auxiliary reagents for froth flotation process are still highly demanding. Herein we report the facile fabrication of a series of polyhedral oligomeric silsesquioxanes (POSS)-based froth flotation giant surfactants via two-step sequentially performed thiol-ene "click" reactions, with precisely-controlled chemical structures and tunable multisite surface functionality. The resulting giant surfactants performed high mineral recovery efficiency in the flotation testing of quartz, hematite and apatite in a broad range of pH conditions. We describe these POSS-based surfactant molecules in an initial proof-of-concept study and propose that this class of giant amphiphiles will be useful in flotation separation technique. Graphical abstract: Image 1 Highlights: Facile and modular preparation of giant surfactants via two step thiol-ene "click" reactions. The exemplary surfactant exhibits promising mineral recovery efficiencies. Only physical adsorption interactions exist during the flotation process.